Uji Toksisitas Ekstrak Daun Ketepeng Cina (Cassia alata L.) pada Keong Mas (Pomacea canaliculata L.) - St. Fatmah, Hiola; Arsad, Bahri (Fakultas MIPA UNM, 2010)
This experimental study aimed to analyze the toxicity of the Cassia alata L. leaves extract in Pomacea canaliculata L with the concentration of the extract as independent variable and the mortality of Pomacea as the dependent one. There were two steps in this study: introductory test and main test. Both of them were done to examine LC50 (lethal concentrate) and LT50 (lethal time) using the number of mortality and its velocity during 48 hour observation. Based on the introductory study, we chose concentrate of 2,5 %; 3%; 3,5%; 4%; and 4;5% of the leaves extract for the treatment groups. Control group were not given any extract. Every group of treatment consisted of 50 Pomacea and each treatment was done 5 times so that there were 1500 Pomacea used in this study. Probit analysis was used for this study result. I then be sown that Cassia alata L. leaves extract could cause mortality of Pomacea canaliculata L which occured from 4 hour after the start of the study. The LC50 was 4,290% of leaves extract after 16 hours after the application with regressionÂ slope Y = 2,456 + 4,561X, and the LT50 was 29,834% with Y = 0,047 + 1,976X.